Gingival Melanosis: Diagnosis and Therapy of Its Aesthetic Involvement. Literature Review - Osorio Ayala, Lesly D.; Cantos Tello, Paola M.; Carvajal Endara, Andrea S. (Odovtos - International Journal of Dental Sciences, 2020)
Gingival hyperpigmentation is produced by excessive melanin deposit, generating a dark gum coloring. Although it does not constitute a health issue, in some cases it usually represents an aesthetic problem that can affect psychologically, for which there are currently several treatment alternatives such as: surgery with scalpel, laser therapy, abrasion, cryosurgery, electrosurgery, among others. The aim of this literature review was to analyze the available information about gingival melanosis and the therapeutics that can be applied to improve the appearance of patients with this condition. Articles in English and Spanish, published during the period 2000-2020 in the PubMed, Medline, Scielo, Cochrane and Lilacs databases, were reviewed. It was concluded that the selection of the technique will depend on each particular case, however, the laser is the most relevant.